2008
DOI: 10.1007/s11274-008-9803-6
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a model of the human proximal colon

Abstract: The objective of the present study was to construct a system that re-creates the conditions of fermentation and absorption of the human proximal colon. The model was constructed using a glass tube with an internal dialysis membrane tube. The food substrate was fed into the dialysis membrane three times a day simulating a typical human feeding. The substrate contained 58% carbohydrates, 35% proteins, 3% fiber, 3% starch, and 1% lipids on dry weight base, with 90% moisture. The inoculum was a fecal culture propa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The total fatty acid content in the colon was insensitive to the presence or absence of the pathogen, although acetic acid levels decreased significantly (P Ͻ 0.05), while butyric acid levels increased significantly (P Ͻ 0.05), in the presence of E. coli O157:H7. Previous studies have suggested that microbial composition and fatty acid differences could be attributed to diet (15,(60)(61)(62)(63), pH (64), the peptide supply (64), and the relative amount of oxygen in the system (65,66). However, these parameters were consistent in this study, suggesting that the altered community structure is impacting the fatty acid composition of the model colon (64,67).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The total fatty acid content in the colon was insensitive to the presence or absence of the pathogen, although acetic acid levels decreased significantly (P Ͻ 0.05), while butyric acid levels increased significantly (P Ͻ 0.05), in the presence of E. coli O157:H7. Previous studies have suggested that microbial composition and fatty acid differences could be attributed to diet (15,(60)(61)(62)(63), pH (64), the peptide supply (64), and the relative amount of oxygen in the system (65,66). However, these parameters were consistent in this study, suggesting that the altered community structure is impacting the fatty acid composition of the model colon (64,67).…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of each week, the microbial community was taken from the stored glycerol stocks, inoculated into 200 ml colon medium (30), and placed in a shaker-incubator at 200 rpm and 37°C for 24 h. The bacterial suspension was then pumped into the dialysis tube of the model colon (Fig. 1, D) at a rate of 5 ml/min (Masterflex pump; Cole-Parmer, Vernon Hills, IL) (15) (Fig. 1, A).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations